Pendampingan Pengayaan Buku Ajar dengan E-Book dan Multi Media Berbasis AI - Wijirahayu, Suciana; Roza, Emilia; Fathin, Asyam Ahmad (Universitas Mathla'ul Anwar Banten, 2024)
Pengembangan literasi digital dan kreativitas guru di era digital semakin diperlukan. Pengabdian kepada masyarakan (PkM) ini bertujuan untuk meningkatkan kompetensi guru dalam mengembangkan bahan ajar digital berkualitas melalui pelatihan dan pendampingan intensif dengan fokus pada pemanfaatan aplikasi book creator dan chatbot. Program ini berupaya mengatasi kendala teknis yang sering dihadapi melalui sinergi Universitas Muhammadiyah Prof. DR. HAMKA dengan sejumlah sekolah mitra di wilayah Kota Tangerang khususnya di SDI Darul Mukminin. Kami mengembangkan model pembelajaran inovatif berbasis projek yang mengintegrasikan elemen gamifikasi dan kolaborasi. Model ini diharapkan dapat meningkatkan motivasi belajar siswa, mengembangkan karakter, serta mempersiapkan mereka untuk menghadapi tantangan abad 21. Harapannya melalui program PkM ini, minimal 80% peserta termotivasi dan mampu menghasilkan buku ajar digital berkualitas dan menerapkannya dalam pembelajaran sehari-hari sehingga berkontribusi pada peningkatan kualitas pendidikan di Indonesia. The development of literacy and creativity needs teachers and lecturers to continuously improved. There are technical obstacles, namely the ability of teachers is not yet optimal, especially in making digital learning media (e-books) with certain applications, including the book creator. The interest of teachers and lecturers in using digital teaching materials builds the students' character in the schools. This challenge relates to the training and help in writing digital textbooks for teachers and introducing chatbot to increase literacy and develop their creativity in enriching teaching materials. The synergy between educational institutions in various countries also needs to be continued, so mentoring for the development of literacy and creativity of teachers Classroom action research carried out as a follow-up to empowering students so that they can produce models of character development with media that can be applied in blended classes by teachers when teaching online while preparing their students to keep learning. The digital textbooks also equip an introduction to the skills of using Chatbot according to the multimodal e-books produced to increase students' enthusiasm for learning.